Home and Beauty: Thai Middle-class’s Aesthetics and the Changes of Space of their House between the 1980s-2000s - Potjanalawan, Pinyapan; Sattayanurak, Saichol (Journal of Social Sciences Naresuan University, 2021)
This research aims at two purposes: first, to explain the character of the middle-class family which changed their activities and the relationship between the members, second, to explain the dynamic of the emotion of the middle-class family about the aesthetic through the practice of the home decoration and the relation of body and residential space in Thai society. This is qualitative research using the historical method through the primary source and the concept of the emotional regime to analyze. The result of the study is the dynamic of the middle-class family change in the 1980s-2000s. Their house has changed by the rapid shift of social, economic, and political conditions which affected the practice of the home decoration. Especially, the expansion of the house owners in the 1990s altered the diversity of home and decoration. These related to their taste and emotion. The beauty in this sense is the aesthetical value expressed through the home and decoration which is the important space of the middle- class family’s consumption. The pattern of these beauties could categorize to Nouveau rich, conservative, and progressive ideas. However, the middle class’s aesthetics were not just only one but related to the complexity of the consumer market and the plurality of their emotion.